Oh no – not yet another small, stand-alone humanities journal! - Frantsvåg, Jan Erik (Septentrio Conference Series, 2014)
See video of the presentation. Small, stand-alone journals create problems for themselves, their authors and their readers. I will take a short tour of some of these problems. I will then present an outline of how a larger, Nordic, multi-disciplinary humanities and social sciences journal could be organized. They idea is not to sell a project, but to show editors and authors that there could be advantages to starting to think outside the traditional box.